Managing postcaesarean section pain with opioid analgesia and the effect on breastfeeding - Višić, Uroš (Obzornik zdravstvene nege, 2024)
Introduction: Pain after caesarean section is an expected event that can affect the patient's recovery and first attempts at breastfeeding. The aim of this review was to determine the relationship between opioid pain management after caesarean section and support during the first breastfeeding attempts.Methods: A descriptive method was used to conduct a literature search in the PubMed Central, ScienceDirect, and Google Scholar databases, which included literature published between 2013 and 2023. A combination of the following keywords was used in the search: "pain", "delivery", "opioid", "mobilisation" and "nursing". Primary sources were selected according to predefined inclusion and exclusion criteria. The search process and selection are illustrated using the PRISMA diagram. A thematic analysis was conducted by coding the data retrieved. Results: The literature search yielded nine articles addressing the status of opioid pain management and breastfeeding after caesarean section. The results of the literature search were critically appraised using the MML tool. The main content pertained to the outcomes of identifying different interventions for the management of postoperative pain and initiation of breastfeeding after caesarean section. Discussion and conclusion: In general, patients in different countries were found to be at higher risk of inadequate forms of pain management after caesarean section. We also identified the key research gaps that should be addressed to support further public health interventions for more appropriate pain management and the promotion of and support with breastfeeding after caesarean section.
Keywords: bolečina; delivery; mobilizacija; mobilization; nursing; opioidi; opioids; pain; porod; zdravstvena nega